(untitled) (Applied Biological Research, 2012)
This study presents the morphometeric characteristics of canine haemo protozoan, Babesia canis, by using software DP2-BSW (Olympus). Most of the B. canis in erythrocytes were pyriform bodies at an acute angle whereas afew were at obtuse angle. The other erythrocytic stage of B. canis was commonly tetrad with some polymorphic forms including ovoid, amoeboid, elongated, umbrella-like, etc. The micrometric measurements of B. canis piroplasms varied from 2.93 - 5.80 x 2.10 - 3.30 µm and a quartered parasite of 5.1 x 5.4 µm size was also seen. The only species of tick, Rhipicephalus sanguineus, a known vector of B. canis, was recovered from infected dogs.